OPTIMASI PERENCANAAN SISTEM PEMBUMIAN PADA RENCANA PEMBANGUNAN GAS INSULATED SUBSTATION 150 KV PECATU - Quentin MP, Putu; Indra Partha, Cok Gede; Janardana, IGN (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUM, 2020)
The construction of the Gas Insulated Substation (GIS) 150 kV Pecatu is planned by PT. PLN (Persero) to get electricity needs in the area of Pecatu, Badung Regency, Bali Province. The Gas Insulated Substation (GIS) 150 kV Pecatu is located in a hilly area with a texture of limestone rocky soil and the resulting soil type resistance is ? = 263.76 ohm-meter. The results of calculations for the type of earthing system Plates earth resistance value of 0.95 ohms at a cost of Rp. 4,196,000,000, - (Four Billion One Hundred Ninety Six Million Rupiah), for the type of Mesh earthing system no results are obtained <1 ohm and for the Multi Grid-Rod earthing system type the grounding resistance value is 0.876 ohms at a cost of Rp 3,753,120,000, - (Three Billion Seven Hundred Fifty Three Million One Hundred Twenty Thousand Rupiah). The type of earthing system recommended is a Multi Grid-Rod earthing system with a distance between parallel conductors (D) of 1 meter, depth of conductor planting as deep as 4 meters above the ground surface, Rod electrode diameter of 0.015 meters, Rod electrode length of 4 meters and total conductor length of 12500 meters.